2008
DOI: 10.3389/neuro.09.009.2007
|View full text |Cite
|
Sign up to set email alerts
|

PET 6-[18F]fluoro-L-m-tyrosine studies of dopaminergic function in human and nonhuman primates

Abstract: Although positron emission tomography (PET) and the aromatic L-amino acid decarboxylase (AADC) tracer 6-[18 F]fl uoro-L-m-tyrosine (FMT) has been used to assess the integrity of the presynaptic dopamine system in the brain, relatively little has been published in terms of brain FMT uptake values especially for normal human subjects. Twelve normal volunteer subjects were scanned using PET and FMT to determine the range of normal striatal uptake values using Patlak graphical analysis. For comparison, seven adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…The plasma metabolic analyses of 11 C-6MemTyr revealed that the inhibitory action of AADC by carbidopa at 5 mg/kg by mouth may be comparable to that determined by its intravenous administration at 0.15 mg/kg, both of which could be too low to affect the brain uptake of 11 C-6MemTyr in the living brain. Taken together, 11 C-6MemTyr should be useful as a PET probe for presynaptic dopamine imaging, because it can provide the sufficiently high Ki values in the striatum of the living brain even without carbidopa, and its MTGA Ki value was as high as that of 18 F-FmT in the monkey brain (22).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The plasma metabolic analyses of 11 C-6MemTyr revealed that the inhibitory action of AADC by carbidopa at 5 mg/kg by mouth may be comparable to that determined by its intravenous administration at 0.15 mg/kg, both of which could be too low to affect the brain uptake of 11 C-6MemTyr in the living brain. Taken together, 11 C-6MemTyr should be useful as a PET probe for presynaptic dopamine imaging, because it can provide the sufficiently high Ki values in the striatum of the living brain even without carbidopa, and its MTGA Ki value was as high as that of 18 F-FmT in the monkey brain (22).…”
Section: Discussionmentioning
confidence: 93%
“…6-18 F-fluoro-L-m-tyrosine ( 18 F-FmT) has been proposed for presynaptic dopamine imaging (20)(21)(22)(23). 18 F-FmT is decarboxylated to 6-18 F-fluoro-m-tyramine ( 18 F-FmTA) by AADC with a 10-foldgreater affinity than 18 F-FDOPA (21).…”
mentioning
confidence: 99%
“…Future work could aim to identify their functional signifi cance, or whether they are in linkage disequilibrium with an SNP in a functional region. Future work also could consider testing effects of genetic variation in human subjects on presynaptic dopamine using 6-[18F]-Fluoro-m-tyrosine positron emission tomography (PET) (Eberling et al, 2007) or 6-[18F]-fl uorodopa (Heinz et al, 2005) PET while also measuring evoked response to alcohol using fMRI.…”
Section: Discussionmentioning
confidence: 99%
“…For quantitative analysis of 18 F-BCPP-EF, arterial blood samples were obtained every 8 s until 64 s after tracer injection and then at 90 and 150 s and at 4,6,10,20,30,45,60,75, and 90 min. Blood samples were centrifuged to separate plasma and were weighed, and the radioactivity was measured using a g-counter (1480 Wizard; Perkin Elmer).…”
Section: Pet Data Analysismentioning
confidence: 99%
“…PMOD software was also used to calculate the nondisplaceable binding potential (BP ND ) of 11 C-DASB, 18 F-MPPF, and 11 C-PE2I via a simplified reference tissue model (27), with the time-activity curve in the cerebellum applied as the indirect input function, as well as to perform multiple-time graphical analysis of 11 C-6MemTyr (9,22,23,28,29), with the time-activity curve in the occipital cortex applied as the input function (30).…”
Section: Pet Data Analysismentioning
confidence: 99%